Deletion of Lytic Transglycosylases Increases Beta-Lactam Resistance in Shewanella oneidensis - Yin, Jianhua; Sun, Yiyang; Sun, Yijuan; Yu, Zhiliang; Qiu, Juanping; Gao, Haichun (Frontiers in Microbiology, 2018)
Production of chromosome-encoded β-lactamases confers resistance to β-lactams in many Gram-negative bacteria. Some inducible β-lactamases, especially the class C β-lactamase AmpC in Enterobacteriaceae, share a common regulatory mechanism, the ampR-ampC paradigm. Induction of ampC is intimately linked to peptidoglycan recycling, and the LysR-type transcriptional regulator AmpR plays a central role in the process. However, our previous studies have demonstrated that the expression of class D β-lactamase gene blaA in Shewanella oneidensis is distinct from the established paradigm since an AmpR homologue is absent and major peptidoglycan recycling enzymes play opposite roles in β-lactamase expression. Given that lytic transglycosylases (LTs), a class of peptidoglycan hydrolases cleaving the β-1,4 glycosidic linkage in glycan strands of peptidoglycan, can disturb peptidoglycan recycling, and thus may affect induction of blaA. In this study, we investigated impacts of such enzymes on susceptibility to β-lactams. Deletion of three LTs (SltY, MltB and MltB2) increased β-lactam resistance, while four other LTs (MltD, MltD2, MltF and Slt2) seemed dispensable to β-lactam resistance. The double LT mutants ΔmltBΔmltB2 and ΔsltYΔmltB2 had β-lactam resistance stronger than any of the single mutants. Deletion of ampG (encoding permease AmpG) and mrcA (encoding penicillin binding protein 1a, PBP1a) from both double LT mutants further increased the resistance to β-lactams. Notably, all increased β-lactam resistance phenotypes were in accordance with enhanced blaA expression. Although significant, the increase in β-lactamase activity after inactivating LTs is much lower than that produced by PBP1a inactivation. Our data implicate that LTs play important roles in blaA expression in S. oneidensis.